Impact of the injection‐level‐dependent lifetime on Voc, FF, ideality m, J02, and the dim light response in a commercial PERC cell. (21st June 2016) - Hieslmair, Henry; Appel, Jesse; Kasthuri, Jai; Guo, Jason; Johnson, Bayard; Binns, Jeff
Abstract: The injection‐level‐dependent (ILD) lifetime of the silicon wafer impacts many characteristics of the final photovoltaic cell. While efficiency is commonly understood to be impacted by the silicon bulk lifetime (at the maximum power point injection level), this work demonstrates the wide ranging impacts of ILD lifetime on the Voc, the fill factor ( FF ), the diode ideality factor m, and the dim light response. Instead of a two‐diode model, we utilize a boundary + ILD bulk lifetime model to analyze a commercial passivated emitter rear contact (PERC) cell featuring an AlOx dielectric rear passivation. The ILD lifetime is directly measured and used to calculate the bulk recombination current across injection levels. With this boundary + ILD lifetime model, we demonstrate the role of the ILD lifetime on many cell parameters in this PERC cell. For most high efficiency commercial p‐type monocrystalline solar cells, the typically lower bulk lifetime at the maximum power point versus the lifetime at the open circuit point reduces the measured FF and pseudo‐ FF . This work illustrates that for a commercial PERC cell with AlOx rear passivation, the ILD lifetime is the primary mechanism behind reduced FF, ideality factors greater than 1, and the source of the J02 term in the two‐diode model. The crucial implications of this work are not only to better understand commercial PERC cell loss mechanisms but also to encourage a focus on different metrics in cell diagnostics. One such metric is the Voc at 0.1 or 0.05 suns. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This paper attempts to clarify the actual functioning of a solar cell by explaining the various observed cell behaviors resulting from the injection level dependent silicon lifetime. This work illustrates that for a commercial PERC cell with an AlOx rear passivation, the injection level dependent lifetime is the primary mechanism behind ideality factors greater than 1, the need for a J02 term, and is responsible for a reduction of 1% in fill factor.